Choroidal Lymphoma: Diagnostic Value of Combined Indocyanine Green Angiography and Optical Coherence Tomography. (7th February 2023) - Pellegrini, Marco; Preziosa, Chiara; Yaghy, Antonio; Ruben, Megan; Invernizzi, Alessandro; Fung, Adrian T.; Staurenghi, Giovanni; Shields, Carol L.
ABSTRACT: Objective: To compare multimodal imaging findings in patients with choroidal lymphoma (CL). Methods: Multicenter retrospective observational case series. Multimodal imaging features of patients with CL were reviewed with particular attention to the patterns of choroidal infiltration on indocyanine green angiography (ICGA) and optical coherence tomography (OCT). Results: Eighteen eyes of 15 patients were included in this study. Average tumor thickness on ultrasonography was 2.6 mm (range, 1.2-5.7 mm). Choroidal infiltration on ICGA was characterized by multifocal, round areas (300-500 microns diameter) of hypocyanescence in all cases, whereas OCT at the same region disclosed diffuse choroidal infiltration. By OCT, the tumor surface contour was primarily placid (22%), dome-shaped (11%), or undulating (67%). Conclusions: In this analysis of eyes with CL, ICGA demonstrated multifocal sub-millimeter regions of choroidal hypocyanescence whereas OCT documented diffuse choroidal infiltration. This incongruence could be a distinctive diagnostic feature of choroidal lymphoma, assisting with differentiation from other pathological entities.